DEVELOPMENT OF THE INTELLECTUAL SYSTEM "INDEPENDENT SMART ASSISTANT" FOR PEOPLE BY VISUALLY DISABILITY IMPAIRED - D. V. Romashin (Современная наука и инновации)
The study describes a way to solve the problem of good rest recreation and cultural leisure for people with visual impairments disability, namely the development and creation of the Independent Smart Assistant software and its use in the conditions of the resorts of the Stavropol Territory of the Russian Federation. The research project proposes a way to create a unified information system using neural networks to facilitate the performance of independent actions by visually disability impaired people by interacting with motion sensors and GPS modules.